1997
DOI: 10.1007/s004220050319
|View full text |Cite
|
Sign up to set email alerts
|

Colliding saccades evoked by frontal eye field stimulation: artifact or evidence for an oculomotor compensatory mechanism underlying double-step saccades?

Abstract: Abstract. What happens when the goal is changed before the movement is executed? Both the double-step and colliding saccade paradigms address this issue as they introduce a discrepancy between the retinal images of targets in space and the commands generated by the oculomotor system necessary to attain those targets. To maintain spatial accuracy under such conditions, transformations must update 'retinal error' as eye position changes, and must also accommodate neural transmission delays in the system so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…When neurons were recorded in the SC during such colliding saccades (Schlag-Rey et al 1992), their activity followed that expected for the site of FEF stimulation and not the actual saccade made. Thus since there is an apparent conflict between the signals generated by the FEF and SC, the authors conclude that the FEF overrides the signal generated by the SC (Dominey et al 1997). If this were the case, in our experiment FEF stimulation should continue to evoke saccades following SC inactivation.…”
Section: Interaction Of Fef and Scmentioning
confidence: 57%
See 2 more Smart Citations
“…When neurons were recorded in the SC during such colliding saccades (Schlag-Rey et al 1992), their activity followed that expected for the site of FEF stimulation and not the actual saccade made. Thus since there is an apparent conflict between the signals generated by the FEF and SC, the authors conclude that the FEF overrides the signal generated by the SC (Dominey et al 1997). If this were the case, in our experiment FEF stimulation should continue to evoke saccades following SC inactivation.…”
Section: Interaction Of Fef and Scmentioning
confidence: 57%
“…A series of stimulation and recording experiments by Schlag, Schlag-Rey, and their collaborators (summarized in Dominey et al 1997) revealed several features of the interaction of FEF and SC, some of which are directly relevant to the present observations. First, they found that stimulation of FEF produced excitation in SC neurons that had the same vector as the site stimulated in the FEF (Schlag-Rey et al 1992), and this observation was one of the key facts in designing our experiments.…”
Section: Interaction Of Fef and Scmentioning
confidence: 57%
See 1 more Smart Citation
“…The advantage of this strategy is that an electrically evoked signal, which is theoretically equivalent to the visual signal of a real target, bypasses the whole afferent visual pathway, including the retina. In this way it was shown that electrical stimulation, applied at different times during and after natural saccades, evokes compensatory saccades that vary in their dimensions depending on the structure stimulated and the exact timing of stimulation [47][48][49][50][51][52] . From data collected in the FEF 49 , the time course of the EPS was computed using the same method as applied in experiments performed with visual targets.…”
Section: A B Double-step Task C Fmentioning
confidence: 99%
“…Neurophysiological studies suggest that FEF encodes information in an eye-fixed (retinotopic) frame of reference (Bruce et al 1985;Russo and Bruce 1993;Tu and Keating 2000), whereas both unit recording and microstimulation studies suggest that SEF uses multiple reference frames (Dominey et al 1997;Martinez-Trujillo et al 2004;Park et al 2006;Bruce 1996, 2000;Tehovnik et al 2000).…”
Section: Introductionmentioning
confidence: 99%